Uganda: Country brief - HarvestPlus (International Food Policy Research Institute, 2015)
HarvestPlus improves nutrition and public health in Uganda by promoting orange sweet potato that provides more vitamin A and beans that provide more iron in the diet. We work with more than 15 partners drawn from government, business, and civil society.